Failures in sprouts-related risk communication - Paterno, Maria Sol Erdozain; Allen, Kevin J.; Morley, Katija A.; Powell, Douglas A. (My University, 2013)
Nutritional and perceived health benefits have contributed to the increasing popularity of raw sprouted seed products. In the past two decades, sprouted seeds have been a recurring food safety concern, with at least 55 documented foodborne outbreaks affecting more than 15,000 people. A compilation of selected publications was used to yield an analysis of the evolving safety and risk communication related to raw sprouts, including microbiological safety, efforts to improve production practices, and effectiveness of communication prior to, during, and after sprout-related outbreaks. Scientific investigation and media coverage of sprout-related outbreaks has led to improved production guidelines and public health enforcement actions, yet continued outbreaks call into question the effectiveness of risk management strategies and producer compliance. Raw sprouts remain a high-risk product and avoidance or thorough cooking are the only ways that consumers can reduce risk; even thorough cooking messages fail to acknowledge the risk of cross-contamination. Risk communication messages have been inconsistent over time with Canadian and U.S. governments finally aligning their messages in the past five years, telling consumers to avoid sprouts. Yet consumer and industry awareness of risk remains low. To minimize health risks linked to the consumption of sprout products, local and national public health agencies, restaurants, retailers and producers need validated, consistent and repeated risk messaging through a variety of sources.
Keywords: Sprouts; Risk communication; Risk analysis